Factors Related to Consumer Preferences of Halal Certified Restaurants (Case Study in Fast Food Restaurant X) - Yusriyah Alfie Syarifah; Endah Budi Permana Putri (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Currently, many consumers choose restaurants just because of the trend in the community without seeing that the restaurant is certified halal or not. In this case, it makes the emergence of preferences with different factors. The purpose of this study was to analyze factors related to consumer preferences of halal-certified restaurants. The type of research used was Observational with a cross sectional design. The total sample in the study was 138 respondents. The sampling method in this study was Non probability sampling with Accidentally sampling that has met the inclusion criteria. The research instrument used a halal knowledge questionnaire and a consumer preference questionnaire with a statistical test using the Chi Square Correlation Test. The results showed that out of 138 respondents, (63%) were female, (50.7%) were educated in higher education, (46.4%) had sufficient knowledge of halal products, (47.8%) chose facilities and (55.1%) restaurant menus that were not good, and (34.8%) chose to like at halal-certified restaurants. Factors related to consumer preferences of halal-certified restaurants are the completeness factor of restaurant facilities with a result of p value = 0.028 and a factor in the restaurant menu with a result of p value = 0.022. There is no relationship between gender factors, the last education, knowledge of halal products with consumer preferences. Further research is needed with other variables such as income, ease of access to information, restaurant food prices, and restaurant services that can find out factors related to consumer preferences of halal-certified restaurants.